2006
DOI: 10.21608/jpd.2006.45323
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Digestibility, Carcass Traits and Some Blood Constituents of Japanese Quails as Affected by Supplement of Chromium in Growing Rations

Abstract: The present study aimed to the effects of chromium (Cr) supplementation with different levels on growth performance, digestibility nutrients, carcass characteristics, some blood constituents and economic efficiency of the growing Japanese quail. A total number of 450 one-day-old Japanese quail's chicks was used divided randomly into five experimental groups. Each group was distributed by 3 replicates pens containing (30 birds in each) until 6 weeks of age. The 1 st group fed the basal experimental diet without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Economical efficiency of chromium supplemented diets showed an improvement when compared with the control diet. Similar results were obtained by Ezzat et al (2006) reported that the highest value of economical efficiency was obtained for quails fed diet supplemented with chromium up to 800 µg Cr / Kg diet. In conclusion, using 5% alfalfa meal with 1200 or 1800 µg Cr/Kg diet were beneficial in egg production and reducing egg yolk and liver cholesterol contents, and increasing the economical return.…”
Section: Economical Efficiencysupporting
confidence: 90%
See 1 more Smart Citation
“…Economical efficiency of chromium supplemented diets showed an improvement when compared with the control diet. Similar results were obtained by Ezzat et al (2006) reported that the highest value of economical efficiency was obtained for quails fed diet supplemented with chromium up to 800 µg Cr / Kg diet. In conclusion, using 5% alfalfa meal with 1200 or 1800 µg Cr/Kg diet were beneficial in egg production and reducing egg yolk and liver cholesterol contents, and increasing the economical return.…”
Section: Economical Efficiencysupporting
confidence: 90%
“…Similarly, El-Koteat et al (2008) found that egg yolk cholesterol and serum total lipids and cholesterol were significantly (P<0.05) decreased by Cr supplementation of laying hen diets. Also, Ezzat et al (2006) and El-Hommosany, (2008) demonstrated that supplementing the diets of quail and broiler with chromium is beneficial in reducing egg cholesterol.…”
Section: Effect Of Chromiummentioning
confidence: 99%